Comparison of allocation strategies of convalescent plasma to reduce excess infections and mortality from SARS‐CoV‐2 in a US‐like population. Issue 1 (24th November 2022) - Kostandova, Natalya; Drabo, Emmanuel Fulgence; Yenokyan, Karine; Wesolowski, Amy; Truelove, Shaun; Bloch, Evan M.; Tobian, Aaron A. R.; Vassallo, Ralph R.; Bravo, Marjorie D.; Casadevall, Arturo; Lessler, Justin; Lau, Bryan
Abstract: Background: While the use of convalescent plasma (CP) in the ongoing COVID‐19 pandemic has been inconsistent, CP has the potential to reduce excess morbidity and mortality in future pandemics. Given constraints on CP supply, decisions surrounding the allocation of CP must be made. Study Design and Methods: Using a discrete‐time stochastic compartmental model, we simulated implementation of four potential allocation strategies: administering CP to individuals in early hospitalization with COVID‐19; administering CP to individuals in outpatient settings; administering CP to hospitalized individuals and administering any remaining CP to outpatient individuals and administering CP in both settings while prioritizing outpatient individuals. We examined the final size of SARS‐CoV‐2 infections, peak and cumulative hospitalizations, and cumulative deaths under each of the allocation scenarios over a 180‐day period. We compared the cost per weighted health benefit under each strategy. Results: Prioritizing administration to patients in early hospitalization, with remaining plasma administered in outpatient settings, resulted in the highest reduction in mortality, averting on average 15% more COVID‐19 deaths than administering to hospitalized individuals alone (95% CI [11%–18%]). Prioritizing administration to outpatients, with remaining plasma administered to hospitalized individuals, had the highest percentage of hospitalizations averted (22% [21%–23%] higher than administering to hospitalized individuals alone). Discussion: Convalescent plasma allocation strategy should be determined by the relative priority of averting deaths, infections, or hospitalizations. Under conditions considered, mixed allocation strategies (allocating CP to both outpatient and hospitalized individuals) resulted in a larger percentage of infections and deaths averted than administering CP in a single setting.